2015
DOI: 10.1186/s12881-015-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel domain-specific POU3F4 mutations are associated with X-linked deafness: examples from different populations

Abstract: BackgroundMutations in the POU3F4 gene cause X-linked deafness type 3 (DFN3), which is characterized by inner ear anomalies.MethodsThree Turkish, one Ecuadorian, and one Nigerian families were included based on either inner ear anomalies detected in probands or X-linked family histories. Exome sequencing and/or Sanger sequencing were performed in order to identify the causative DNA variants in these families.ResultsFour novel, c.707A>C (p.(Glu236Ala)), c.772delG (p.(Glu258ArgfsX30)), c.902C>T (p.(Pro301Leu)), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…Last but not the least, DFNX3 has already been diagnosed in molecular level, so POU3F4 gene should be screened in the outpatient persons who have the clinical phenotypes of DFNX3. [272829] Our study also has some limitations. On one hand, more pedigree and sporadic people should be recruited.…”
Section: Discussionmentioning
confidence: 96%
“…Last but not the least, DFNX3 has already been diagnosed in molecular level, so POU3F4 gene should be screened in the outpatient persons who have the clinical phenotypes of DFNX3. [272829] Our study also has some limitations. On one hand, more pedigree and sporadic people should be recruited.…”
Section: Discussionmentioning
confidence: 96%
“…The first gene identified for a non-syndromic X-linked form of hearing loss was the gene POU3F4 located in the DFNX2 locus [84]. Nance et al in 1971 [85], described DFNX2 as a recessive X-linked condition characterized in males by profound mixed hearing loss, vestibular abnormalities and congenital fixation at the stapes with perilymphatic gusher.…”
Section: Non-syndromic Sensorineural Hearing Lossmentioning
confidence: 99%
“…Molecular genetic studies of congenital deafness in Nigeria revealed that mutations in the known deafness genes [ GJB2 (MIM 121011) , GJB6 (MIM 604418) , SLC26A4 (MIM 605646)] that are common in Europe and America are uncommon among Nigerian deaf patients (Lasisi, Bademci, Foster, Blanton, & Tekin, ). Subsequent studies identified a novel mutation responsible for X‐linked deafness—c.987T>C (p.Ile308Thr) in POU3F4 (MIM 300039), the first novel deafness gene among Nigerians (Bademci et al., ). An ongoing collaborative project is studying the genomics of CHD in Lagos using an approach that includes chromosomal array screening, whole exome capture and sequencing (WES) as well as functional studies.…”
Section: Genetics Research In Nigeriamentioning
confidence: 99%